EFEK KONSENTRASI Cu PADA STRUKTUR DAN SIFAT HANTARAN LISTRIK NANOPARTIKEL CuPt - Imamora, Marjoni; R, Setia Erlila; Rahmi, Elvy; Maiyena, Sri; Umar, Akrajas Ali (Sainstek : Jurnal Sains dan Teknologi, 2015)
The investigation of bimetallic CuPt Nanoparticles (CuPt NPs) with average diameters in the 196.7±98 nm range have been prepared by the Liquid phase deposition methods and synthesized directly on an indium tin oxide (ITO) substrate. CuPt NPs with  high surface defect grown on (ITO) surface were prepared via a simple immersion of the substrate into a solution contains 1 mM Potassium Hexachloro Platinate (K2PtCl6), 0.2 mM Anhydrous Copper (II) Sulfate (CuSO4) anhydrous, 0.01 M Sodium dodecyl sulfate (SDS) and 10 mM Formic acid for 4 h at room temperature. The modification of Cu2+ ion precursor play a role to determine the nanoparticles geometry obtained. The simultaneous reduction of metal ions leads to either a surface enriched with one component or an alloy type of structure depending on the bimetal composition. The bimetallic CuPt NPs dispersions are characterized by FESEM, EDX Mapping, XRD, HRTEM and XPS analysis.Key words: CuPt, Liquid phase deposition, Bimetallic CuPt NPs